wildcard ssl certificate
2023 Mathematics Competition

Question 18

  • Mathematics
  • Maths
  • Competition
  • 2023

5 comments

6(x-1)+4(x+4)(x-1)=2x+2(x+4)
6x-6+4x²+12x-16=2x²+8x+2x+8
2x²+8x-30=0
x²+4x-15=0
Using quadratic formula
x=-4±√(16+60)/2
x=4±√(76)/2

Caleb Adeleye
1 year ago

Congratulations @Akinola Ajayi, please check your wallet

Akinola Ajayi
1 year ago

Multiply each term by (x+4)(x-1)
6(x-1) +4(x+4)(x-1) =(2x+2)(x+4)
6x-6 + 4x² -4x +16x -16 = 2x² +8x +2x +8
Collect likes terms
4x² -2x² +6x -4x +16x -8x -2x -6 -16 -8=0
2x² +8x -30
Solving using quadratic formula
X=-2±√19

Akinola Ajayi
1 year ago

-2±√19

Progress Ejiro
1 year ago

X=√11
Or X=3.3